Flexural strengthening of LVL beam using CFRP. (30th September 2017) - Subhani, Mahbube; Globa, Anastasia; Al-Ameri, Riyadh; Moloney, Jules
Highlights: Bending tests on LVL beams using two configuration of externally bonded CFRP. Effectiveness of CFRP is limited by the fibrous failure of LVL under tension. Analytical model considering non-linearity of wood under compression. Abstract: Laminated veneer lumber (LVL) is one of the major construction material in Australia as well as other parts of the world. To increase its load carrying capacity, various internal and external methods of applying fibre reinforced polymer (FRP) can be found in the literature. In this article, carbon FRP (CFRP) is used externally on the tension side of LVL beams to enhance its flexural capacity. Two types of bonding arrangements are considered in this study, and the improvement in terms of ductility, stiffness and ultimate load carrying capacity against control beams are investigated. In addition, the experimental data is verified using two analytical models. One of the analytical models considers elastic-plastic behaviour of timber in compression while the other contemplates the non-linear behaviour. The advantages and accuracy of both models are assessed for the application in the design of a CFRP-LVL composite beam.